ENO2 Affects the Seed Size and Weight by Adjusting Cytokinin Content and Forming ENO2-bZIP75 Complex in Arabidopsis thaliana - Liu, Zijin; Zheng, Lamei; Pu, Li; Ma, Xiaofeng; Wang, Xing; Wu, Yu; Ming, Hainan; Wang, Qing; Zhang, Genfa (Frontiers in Plant Science, 2020)
Arabidopsis thaliana ENO2 (AtENO2) encodes two proteins AtENO2 (enolase) and AtMBP-1 (c-Myc binding protein 1-like). The loss of AtENO2 function causes the constitutive developmental defects which are correlated with reduced enolase activity, but not AtMBP-1 transcript abundance. However, the regulation mechanism of AtENO2 on the seed properties is still not clear. In this study, we found that the mutation of AtENO2 reduced the seed size and weight. The level of glucose in seed was significantly elevated but that of starch was decreased in AtENO2 mutants compared to WT plants. We also found that AtENO2 mutation reduced the content of cytokinin which resulted in smaller cotyledons. The RNA-seq data showed that there were 1892 differentially expressed genes and secondary metabolic pathways were significantly enriched. Instead of AtMBP-1, AtENO2 protein interacted with AtbZIP75 which may mediate the secondary metabolism. Therefore, ENO2 alters the size and weight of seeds which is not only regulated by the content of cytokinin and secondary metabolism, but may be affected by the interaction of ENO2 and bZIP57. These results are helpful to understand the novel function of AtENO2 which provide a foundation for further exploration of the key candidate genes for crop breeding.